EMERGENCY ASSISTANCE FOR THE HOSPITALIZED PATIENT IN THE INTENSIVE CARE UNIT (Fiep Bulletin - online, 2014)
To reach the quality in the assistance it must be had the knowledge and the manuscript of the resources, the trained employees and chemical preparations so that they can really develop quality in the assistance.It was through this present time that we carry through a research in the Unit of Intensive Therapy of a Hospital of Curitiba city. The objective was to identify the existence of emergency in the assistance to the patient, and if the employees worry about the quality in the assistance, and identify the functions of the nurse in the UTI.The used methodology was of qualitative character. The results in had shown them that it was possible to identify the quality of the services given in the UTI and that the employees if worry about the emergency in the given quality the patient.
Keywords: Emergency; quality in the assistance; humanization